Globalization Seen from the Margins: Indigenous Ecuadorians and the Politics of Place - Clark, A. Kim (Anthropologica, 2022)
Processes of economic globalization over the last quarter century, associated with increased mobility of capital, goods and labour, suggest that attachments to place are of decreasing importance. However, this may be a result of looking at these processes from the centre, rather than from the margins. This article combines a discussion of how globalization and the debt crisis in Ecuador have restructured the limits of the possible for subaltern groups, with a consideration of some of the unexpected consequences of those processes in the countryside, as broad economic processes intersect with local histories and human agency.